Cessante Causa, Cessat Effectus : Cure is only Possible by Hering’s Law of Cure and with Annihilation of Existing Miasmatic Manifestation (Advancements in Homeopathic Research, 2023)
Skin diseases in homoeopathy are regarded as Mother of all chronic diseases, so it is not neglected and considered as Causa prima - Hahnemann’s psoric manifestation and of high importance in homoeopathic totality, if found as a cause or existing along with main manifestation or alternating with other disease such as bronchial asthma etc. Similarly skin disease suppression by external application or even only by acute totality or sector totality selected homoeopathic medicine is considered of high important in miasmatic totality. This article deals with three cases where in one case skin eruption alternating with bronchial asthma and other case is having suppression of skin disease resulted to primary amenorrhoea. The last case is the case of an lady who had long back nose and its below area eruptions and subsequent ulcers suppressed by Nitric acid 10000CH caused the allergic conjunctivitis and skin allergies with lot of blackish discolurations and itching in whole body. The treatment methodology is adopted as per Hahnemann’s concept of treatment of chronic diseases i.e. Cessante causa, cessat effectus and Hering’s law of cure. The 1st case deals with Hering’s law of cure whereas 2nd case and 3rd case deals with Cessante causa, Cessat effectus. The three cases deals with practical part of taking acute totality and constitutional totality for total cure.
Keywords: Eruptions; Suppressions; Acute totality; Constitutional totality; Bronchial asthm; Amenorrhoea